Reactionaries of the lectern: Universalism, anti-empiricism and corporatism in Austrian (and German) social theory. (May 2021) - Scott, Alan; Rief, Silvia
This article discusses one early manifestation of a recurring theme in social theory and sociology: the relationship between general ('universal' or 'grand') theory and empirical research. For the early critical theorists, empiricism and positivism were associated with technocratic domination. However, there was one place where the opposite view prevailed: science and empiricism were viewed as forces of social and political progress and speculative social theory as a force of reaction. That place was Red Vienna of the 1920s and early 1930s. We examine how this view came to be widespread among Austro-Marxists, empirical researchers and some members of the Vienna Circle. It focuses on the arguments and institutional power of their opponents: reactionary, universalistic and corporatist social theorists. The debate between Catholic corporatist theory and its empiricist critics is located not merely in Vienna but also within wider debates in the German-speaking world. Finally, we seek to link these lesser-known positions to more familiar strands of social thought, namely, those associated with Weber and, more briefly, Durkheim and Elias.